What design education tells us about design theory: a pedagogical genealogy. Issue 4 (2nd October 2019) - Ghajargar, Maliheh; Bardzell, Jeffrey
ABSTRACT: In design theory, we often come across scholarly efforts that seek to define design as a unique discipline and to characterize it as a distinct category of practice, with its own epistemology in that it differs from sciences, arts and humanities (Cross, N. 2011. Design Thinking: Understanding How Designers Think and Work . Oxford: Berg.; Dorst, K. 2015. Frame innovation: Create New Thinking by Design . Cambridge: The MIT Press. Nelson, H. G., and E. Stolterman. 2012. The Design Way: Intentional Change in an Unpredictable World . The MIT Press.; Redström, J. 2017. Making Design Theory . MIT Press.). Although such efforts are helpful in teasing forward the nature of design epistemologies and practices, we question them by critically engaging with epistemic paradigms informing design education, its structural forms, origins and purposes, historically, while suggesting the time has come to reevaluate design's relationships with other epistemological traditions, including the sciences and humanities. We unpack history of design education, in order to problematize what we have come to view as overly schematized epistemological distinctions, most notably the asserted opposition between (what Schön calls) technical rationality and an alternative epistemology broadly linked to pragmatism and/or phenomenology. We do so by offering a genealogy of design education showing that since the nineteenth century, design programmes have continuously, if diversely, taught novice designers, methods, crafts, and attitudes that reflect diverse epistemological traditions. Theorists and educators of design have a shared interest in balancing the needs to appreciate and help develop that which is distinctive of design and also to build upon design's rich epistemological connections to the sciences and humanities. Whereas the former helps the field improve its abilities to contribute to society, the latter provides many of the theoretical, methodological, and pedagogical resources that make such contributions possible.